Surface‐enhanced Raman scattering characteristics of CuO : Mn/Ag heterojunction probed by methyl orange: effect of Mn2+ doping. (17th March 2016) - Prakash, Om; Kumar, Shiv; Singh, Pushkar; Deckert, Volker; Chatterjee, S.; Ghosh, A.K.; Singh, Ranjan K.
Abstract : Interest in the synthesis of hybrid substrates for surface‐enhanced Raman scattering (SERS) has surged recently. Hereof, in the present work, a hybrid SERS substrate CuO : Mn/Ag heterojunction has been synthesised. To accomplish this, the nanostructred Ag island film and CuO : Mn nanoparticles are synthesised by vacuum thermal evaporation method and sol–gel method respectively, and thereafter, a heterojunction between the CuO : Mn and Ag is fabricated by adsorption of CuO : Mn (10 ‐3  m in ethanol) on Ag island film. Further, the SERS sensitivity of CuO : Mn/Ag heterojunctions has been studied by probing methyl orange. We observed that with Mn‐doping in the lattice of CuO, the SERS signal is enhanced considerably because of ferromagnetic ordering in CuO : Mn. DFT/B3LYP/6‐311 G(d, p) method is used to calculate the energy of HOMO and LUMO level of methyl orange. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A hybrid surface‐enhanced Raman scattering substrate CuO : Mn/Ag heterojunction has been fabricated and investigated the effect of Mn 2+ doping on the surface‐enhanced Raman scattering bands.